Effect of Brain Gym ® exercises on cognitive function and brain-derived neurotrophic factor plasma level in elderly: a randomized controlled trial - Adriani, Donna; Imran, Yudhisman; Mawi, Martiem; Amani, Patwa; Ilyas, Ermita I.I. (Universa Medicina, 2020)
BackgroundCognitive impairment and dementia are some of the major health concerns in the aging population. Many studies showed positive effects of physical exercise in delaying or preventing these conditions. Brain Gym ® exercises is a structured aerobic exercise involving head, eyes and crossing movements of the extremities in order to stimulate both brain hemispheres. This study was conducted to evaluate the effect of Brain Gym ® exercises sessions on cognitive function and plasma brain-derived neurotrophic factor (BDNF) in the elderly.MethodsA non-blinded randomized controlled study involving 64 healthy women aged >60 years who were randomized into Brain Gym ® exercises treatment group (n=32) and control group (n=32). Treatment group joined 60 minutes of brain gym exercises sessions twice a week for 12 weeks. The measured outcomes were cognitive function (assessed by mini-mental state examination [MMSE] questionnaire) and plasma BDNF levels. The outcomes were measured at base-line and after the intervention. An independent t-test was used to analyze the data.ResultsThe BDNF levels were increased in both groups after 12 weeks, and there was a significant difference between treatment group (41.26 ± 6,82 ng/mL) and control group (37.10 ± 8.11 ng/mL)(p=0.040). However, the MMSE score was not significantly different between the two groups (p=0.200).ConclusionBrain Gym ® exercises sessions significantly increase plasma BDNF level in the elderly population. In practical terms, we may suggest evaluation of the effects of Brain Gym ® exercises as a strategy in the treatment of disorders associated with central degenerative changes.